Learning Arabic Speaking (Kalam) through Thorndike’s Behaviorism: Pedagogical Implications for AI-Assisted Learning - Mulia Daulay, Andhika; Mia Nurmala; Yusuf Ali Tantowi (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study investigates the implementation of Arabic speaking instruction in Thorndike’s behaviorism principles (law of readiness, law of exercise, and law of effect) at SMPIT Imam An-Nawawi Pekanbaru and explores their pedagogical implications for AI-assisted language learning. Using a qualitative case study design, the research involved classroom observations, semi-structured interviews, and documentation in Arabic speaking classes. The findings reveal that law of readiness was reflected through verbal stimulation and guided prompting that prepared students’ speaking engagement, while law of exercise appeared through repetition, drilling, and repeated speaking interaction that gradually formed students’ speaking habits. In addition, law of effect was implemented through positive reinforcement, corrective feedback, and motivational responses that strengthened students’ speaking confidence and verbal participation. The study also found that pedagogical mechanisms identified in the classroom, such as repetition, adaptive prompting, corrective feedback, and reinforcement-based interaction, conceptually align with the learning logic used in contemporary AI-assisted language learning systems. The study concludes that Thorndike’s behaviorism remains pedagogically relevant in Arabic speaking instruction and offers conceptual insights for the development of AI-assisted Arabic language learning, particularly in speaking habit formation and adaptive verbal interaction.